Introduksi Racikan Minuman Herbal Keluarga Dawis 1 RT 03/24 Jebres Surakarta Sebagai Edukasi Dalam Menjaga Imunitas - Novian Wely Asmoro; Afriyanti Afriyanti; Catur Budi Handayani (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The Covid-19 pandemic has brought changes and new habits in society. Covid-19 cases in Indonesia and the world are still increasing, so it is very worrying. One effort that can be made to avoid viral infections and diseases including Covid-19 is to maintain immunity through the consumption of functional foods containing bioactive substances such as empon-empon, ginger, Moringa leaves, lemon, honey, etc. Dasawisma 1 (Dawis 1) at RT 03/24 Jebres Subdistrict Jebres Surakarta District is one of the target partners to be given knowledge and understanding of efforts to maintain body immunity with the introduction of family herbal drinks. The method is carried out through several stages of activity, namely Phase I, Counseling, Delivery of Materials, Brochures & Posters of Healthy Food Keeping Immune. Phase II, Delivery of Concoction Materials & Benefits of Family Herbal Drinks. Stage III, Introduction & Practice of Family Herbal Drinks Manufacturing. Activity evaluation using pretest, postest and practical assessment methods. The indicators of the success of the activities are the increase in the average value of partners, the involvement of partners and the ability of partners to practice making family herbal beverage products.